Modeling the process of skidding wood under the canopy of a forest plantation (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The study examines the issue of skidding wood using small-sized mechanized skidding tools in areas of a forest plantation created artificially according to a known scheme for placing trees in it. The basis is the conditions of evenly gradual felling or similar to them, when skidding wood must be performed between the trees that remain on the area. The purpose of the study is to create a model of an artificial forest plantation and a mathematical model of the kinematics of the skidding system in it and to develop a simulation computer model of the skidding system movement in the plantation on their basis.The basis for implementing the study goal is mathematical modeling, which is based on the basic laws of theoretical mechanics and physics. At the same time, the technical capabilities of a small-sized skidding tool, the physical properties of the object of work and the method of its fixation on the skidding tool are taken into account and reflected. The main features of the skidding system's operating environment that will affect its kinematics and overall dimensions are taken into account.The result of the research is a model of an artificial forest stand, a mathematical model of the kinematics of a small-sized skidding system with a description of partial cases, its numerical implementation, and a computer model for simulating the movement of the skidding system in the stand.
Keywords: round timber; kinematics; skidding system; artificially created forest stand; modeling; small-sized mechanized skidding device